The Relationship Between the Number of Partus and the Level of Education of Mothers Towards Exclusive Breastfeeding in the Working Area of the Telaga Biru Health Center - Harismayanti Harismayanti; Ani Retni; Sri Yulian Hunow; Dhea Safitri Didik Hariyanto (Universitas Ibn Khaldun Bogor, 2023)
Lack of exclusive breastfeeding in infants has an impact on the cognitive development and physical growth of children such as stunted brain growth, and stunted physical growth so that children become stunted, children become weak and easily sick. Exclusive breastfeeding in Gorontalo Province (2018) amounted to 46.91%. The purpose of the study was to determine the number of partus and the level of education of mothers towards exclusive breastfeeding. Quantitative research design with cross-sectional approach. The population amounted to 54 infants with the same number of samples, namely 54 respondents. The results showed that the highest number of partus was primipara as many as 31 people with a value of pValue = 0.014<0.05 and the highest maternal education was secondary education (junior high and high school) as many as 36 people with a value of pValue = 0.000< 0.05. Conclusions are related to the number of partus and the level of education of mothers to exclusive breastfeeding in the working area of the Telaga Biru Health Center. Suggestions are expected to be input for the puskemas in increasing the scope of exclusive breastfeeding and can add information for mothers to provide exclusive breastfeeding to their children.